2020
DOI: 10.1111/jipb.12915
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids regulate outer ovule integument growth in part via the control of INNER NO OUTER by BRASSINOZOLE‐RESISTANT family transcription factors

Abstract: Brassinosteroids (BRs) play important roles in regulating plant reproductive processes. BR signaling or BR biosynthesis null mutants do not produce seeds under natural conditions, but the molecular mechanism underlying this infertility is poorly understood. In this study, we report that outer integument growth and embryo sac development were impaired in the ovules of the Arabidopsis thaliana BR receptor null mutant bri1‐116. Gene expression and RNA‐seq analyses showed that the expression of INNER NO OUTER (INO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…This phenotype, which was also found in BR mutants det2-1 and bri1-5, was due to a reduction in both cell length and number. Moreover, the bzr1-1D mutation was able to partially restore bri1-116 defects in outer integument growth (Jia et al, 2020), suggesting that BZR1 mediates the BRI1 outer integument growth regulation. According to this, in the sextuple null mutant of the six BZRs encoded in Arabidopsis, bzr-h, outer integument growth was completely arrested after initiation.…”
Section: Third Step: Integument Morphogenesismentioning
confidence: 97%
See 4 more Smart Citations
“…This phenotype, which was also found in BR mutants det2-1 and bri1-5, was due to a reduction in both cell length and number. Moreover, the bzr1-1D mutation was able to partially restore bri1-116 defects in outer integument growth (Jia et al, 2020), suggesting that BZR1 mediates the BRI1 outer integument growth regulation. According to this, in the sextuple null mutant of the six BZRs encoded in Arabidopsis, bzr-h, outer integument growth was completely arrested after initiation.…”
Section: Third Step: Integument Morphogenesismentioning
confidence: 97%
“…According to this, in the sextuple null mutant of the six BZRs encoded in Arabidopsis, bzr-h, outer integument growth was completely arrested after initiation. Moreover, both BRI1 and BZR1 were broadly localized in all ovule tissues from stage 2-I to stage 3-V, including the initiated and out-growing outer integument cells (Jia et al, 2020). Interestingly, using RNA-seq transcriptomic analysis, Jia et al (2020) found that INO, which regulates outer integument development (Villanueva et al, 1999), is upregulated in the ovules of bri1-116 bzr1-1D when compared with bri1-116.…”
Section: Third Step: Integument Morphogenesismentioning
confidence: 99%
See 3 more Smart Citations